Interactive Software-based Modeling for Gait Analysis of Musculoskeletal Structures - Mirza, Nada Masood; Ali, Adnan; Ishak, Mohamad Khairi (UI Scholars Hub, 2022)
Software for interactive musculoskeletal modeling applies diverse scientific and technological concepts to stimulate the movement of musculoskeletal figures. Several tools are available for biomechanical analysis in studying motion and capturing the musculoskeletal representation data to facilitate further evaluation for muscle activation. Musculoskeletal software, such as the OpenSim model, animates, and measures in 3D the structural movement of bones, muscles, joints, ligaments, and such structures in the human body. Users apply graphical interfaces to manipulate the movement science for fast and accurate analysis. OpenSim simulation software features a user-friendly interface to allow the proper clinical application in biomechanics and rehabilitation research. The exploitation of the potential features and outputs is significant to optimize electromyography technology for musculoskeletal simulation. Emphasis on testing fundamental hypotheses with posture experimentation and simulation encourages the adoption of OpenSim in various biomechanical models.